2018
DOI: 10.1038/s41598-018-25166-5
|View full text |Cite
|
Sign up to set email alerts
|

First long-term detection of paleo-oceanic signature of dust aerosol at the southern marginal area of the Taklimakan Desert

Abstract: We firstly conducted a long-term in-situ field measurement at a marginal area (Hotan) of the southern Taklimakan Desert covering all four seasons. Detailed chemical characterization of dust aerosol over Hotan showed several unconventional features, including (1) ubiquity of high Na+ and Cl− abundances in the Taklimakan dust aerosol and its Cl−/Na+ ratio close to seawater; (2) high Ca content in the Taklimakan dust (7.4~8.0%) which was about two times of that in the natural crust; (3) high abundance of soluble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…They are categorized into two origins; primary particles are emitted directly in solid or liquid form into the atmosphere space. Primary aerosol particles are natural sources (Peacock, 2008) such as volcanic ash particles (Arnalds et al, 2013; Butwin et al, 2018), and deserts and oceans (Reynolds et al, 2017; Zhou et al, 2018). The deserts are usually wind-driven dust particles from the pool of soil.…”
Section: Introductionmentioning
confidence: 99%
“…They are categorized into two origins; primary particles are emitted directly in solid or liquid form into the atmosphere space. Primary aerosol particles are natural sources (Peacock, 2008) such as volcanic ash particles (Arnalds et al, 2013; Butwin et al, 2018), and deserts and oceans (Reynolds et al, 2017; Zhou et al, 2018). The deserts are usually wind-driven dust particles from the pool of soil.…”
Section: Introductionmentioning
confidence: 99%
“…All water-soluble ion contents in the laboratory-generated dust aerosols and bulk soil samples are shown in Table S1. Table summarizes the results of the laboratory-generated dust aerosols, also compared with those of ambient dust collected over the Taklamakan Desert. The average contents of SO 4 2– , Ca 2+ , Mg 2+ , and K + are similar in the gravel dust and sand dust; they ranged from 2% to 4%, 1.4% to 4%, 0.2% to 0.3%, and 0.2% to 0.3%, respectively. These values were similar to that in the ambient dust aerosol collected over the Taklamakan Desert, which averaged 2%–5%, 0.6%–5%, 0.01%–0.4%, and 0.1%–0.2%.…”
Section: Resultsmentioning
confidence: 99%
“…High sulfate concentrations (3%–4% of mineral dust mass) have always been observed in dust aerosols over the Taklamakan Desert. , Wu et al investigated the origin of these dust sulfates and concluded that they were substantially derived from surface soil in the desert area. Arid salt lakes or saline–alkaline lands distributed in the basin contain soluble salts and are thought to be the possible source of these salts. , However, these regions are not widely distributed in the basin, and the salts they release do not explain why dust aerosols always contain high sulfate levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation